The Murder of Shireen Abu Akleh: How Does Law Protect the Journalist in a War? - Gunawan, Yordan; Ihsan, Fawaz Muhammad; Anderson, Paulo Andres (Lex Scientia Law Review, 2023)
Shireen Abu Akleh, an esteemed Al Jazeera journalist, was sadly killed by Israeli army gunfire in May 2022 while reporting on the Israel-Palestine military war. To pursue justice for this horrific act, the Palestinian administration filed a formal complaint with the International Criminal Court (ICC). Despite the presence of strong proof, the Israeli government maintains that the charges are false. This study looks thoroughly into the Abu Akleh murder case, examining it from the standpoint of international law. Using normative legal research methods, the paper thoroughly examines the historical features of the murder as well as the legal procedures specified by international law to assure the administration of justice. Furthermore, the study emphasizes the critical importance of the Palestinian government's ICC complaint as a critical first step in initiating the judicial procedure. Notably, the United Nations has formally declared the Israeli army guilty of Abu Akleh's death, heightening the gravity of the situation. This research states categorically that the Israeli government must be held liable for this heinous act after exhaustively evaluating the most recent facts and prestigious international legal frameworks. It is fervently hoped that by unraveling the multifaceted dimensions inherent in this case, justice will ultimately prevail, steadfastly reaffirming the indispensable principles that safeguard press freedom and protect journalists worldwide, including within Indonesia as an integral member of the international community.